2014
DOI: 10.1002/joc.3987
|View full text |Cite
|
Sign up to set email alerts
|

Interdecadal modulation of ENSO teleconnections to the Indian Ocean Basin Mode and their relationship under global warming in CMIP5 models

Abstract: On the basis of Coupled Model Intercomparison Project phase 5 (CMIP5) models, this study have examined the ability of models to capture the El Niño/Southern Oscillation (ENSO)-Indian Ocean Basin Mode (IOBM) relationship, and investigated the characteristics of interdecadal change of ENSO-IOBM relationship as well as the response of the ENSO-IOBM relationship to the global warming. Among 23 CMIP5 models, the capability of models in representing the IOBM depends largely on the simulation of ENSO. Moreover, half … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 94 publications
1
35
0
Order By: Relevance
“…and surface humidity strengthen tropospheric temperature anomalies and NWP anomalous anticyclone than in the present, and the enhanced NWP anomalous anticyclone in turn leads to increased TIO ! , suggesting the positive feedback strengthens, consistent with Tao et al (2014). Indeed, we find that both TIO !…”
Section: B the Change Ofsupporting
confidence: 86%
“…and surface humidity strengthen tropospheric temperature anomalies and NWP anomalous anticyclone than in the present, and the enhanced NWP anomalous anticyclone in turn leads to increased TIO ! , suggesting the positive feedback strengthens, consistent with Tao et al (2014). Indeed, we find that both TIO !…”
Section: B the Change Ofsupporting
confidence: 86%
“…The Indian Ocean is home to some of the warmest water in the world's ocean, exceeding 28°C (Tao et al, ). Therefore, deep convection is active over this warm water and is a key source for atmospheric teleconnections into both hemispheres (Xie et al, ).…”
Section: Enso Teleconnections Impacted By Ocean Basins Outside the Trmentioning
confidence: 99%
“…ENSO impacts are modulated by the IOD in the Northern and Southern extratropics during boreal winter (Saji & Yamagata, ; Tao et al, ). For example, wave trains like the PNA and the PSA are prominent during El Niño in the boreal winter when accompanied by a positive IOD in the previous fall (Figures a and b).…”
Section: Enso Teleconnections Impacted By Ocean Basins Outside the Trmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many studies have suggested a decadal variability of ENSO (Gershunov and Barnett, 1998;Wang and Picaut, 2004;Leloup et al, 2007) and/or IOD (Ashok et al, 2004;Abram et al, 2008;Ummenhofer et al, 2011) characteristics, as well as their interactions (Yuan and Li, 2008;Xie et al, 2010;Huang et al, 2010;Chowdary et al, 2012;Tao et al, 2014). The lag correlation between STIO SSTA in fall and Niño 3.4 SSTA in the following fall has been shown to be subjected to decadal variations in both observations and in historical simulations of the coupled climate models of the phase fi ve Coupled Model Intercomparison Project (CMIP5) (Xu et al, 2013, manuscript).…”
Section: Introductionmentioning
confidence: 99%